COVID-19, paradoxes, and new business models. An opportunity for third sector organizations? (European journal of volunteering and community-based projects, 2021)
The Covid-19 pandemic has impacted several business fields, besides the healthcare sector. The new situation calls for new challenges, with several organizations needing to rethink their business models. Using an EFTE (estimate, feedback, talk, estimate) approach, the article presents 50 paradoxes to rethink post-pandemic business models, highlighting those most suitable for third sector organizations.
Keywords: Business models; third sector organizations; covid-19